2021
DOI: 10.3390/nu13061754
|View full text |Cite
|
Sign up to set email alerts
|

Brown Seaweed Sargassum siliquosum as an Intervention for Diet-Induced Obesity in Male Wistar Rats

Abstract: The therapeutic potential of Sargassum siliquosum grown in Australian tropical waters was tested in a rat model of metabolic syndrome. Forty-eight male Wistar rats were divided into four groups of 12 rats and each group was fed a different diet for 16 weeks: corn starch diet (C); high-carbohydrate, high-fat diet (H) containing fructose, sucrose, saturated and trans fats; and C or H diets with 5% S. siliquosum mixed into the food from weeks 9 to 16 (CS and HS). Obesity, hypertension, dyslipidaemia, impaired glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
1
10
0
1
Order By: Relevance
“…The diet-induced changes in metabolic, cardiovascular and liver parameters in the rat model used in this project mimic the changes in human metabolic syndrome [16]. Interventions with seaweeds have been previously shown to reverse these changes [19][20][21]. This study shows that high-carbohydrate, high-fat diet-fed rats supplemented with the microalgae N. oceanica had higher lean mass and lower abdominal and liver fat than rats fed only the obesogenic diet.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The diet-induced changes in metabolic, cardiovascular and liver parameters in the rat model used in this project mimic the changes in human metabolic syndrome [16]. Interventions with seaweeds have been previously shown to reverse these changes [19][20][21]. This study shows that high-carbohydrate, high-fat diet-fed rats supplemented with the microalgae N. oceanica had higher lean mass and lower abdominal and liver fat than rats fed only the obesogenic diet.…”
Section: Discussionmentioning
confidence: 67%
“…The diet-induced changes in metabolic, cardiovascular and liver parameters in the rat model used in this project mimic the changes in human metabolic syndrome [16]. Interventions with seaweeds have been previously shown to reverse these changes [19][20][21]. The relative abundance of bacteria from the class Bacteroidia and Erysipelotrichia was increased in C and CN rats (Bacteroidia: C, 29.00%; CN, 29.63%; p > 0.05; Erysipelotrichia: C, 9.31%; CN, 8.21%; p < 0.01) compared to H and HN rats (Bacteroidia: H, 17.17%; HN, 12.12%; p > 0.05; Erysipelotrichia: H, 4.35%; HN, 3.93%; p < 0.01).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The animals were fed a diet with or without supplementation of 10% Nannochloropsis gaditana for 2 months. The results showed that the Nannochloropsis gaditana supplementation reduced their blood glucose and HbA1c levels and attenuated the amount of tissue oxidative stress and inflammation, which resulted in the improvements of functions in the liver and kidney of the diabetic rats [ 80 ].…”
Section: Treating Metabolic Diseasesmentioning
confidence: 99%